Predictors of Urinary Continence Recovery after Modified Radical Prostatectomy for Clinically High-Risk Prostate Cancer - Hou, Guo-Liang; Luo, Yun; Di, Jin-Ming; Lu, Li; Yang, Yi; Pang, Jun; Si-tu, Jie; Gao, Xin (Urology Journal, 2015)
Abstract Purpose: To retrospectively determine predictors of urinary continence (UC) recovery in clinically high-risk prostate cancer (PCa) patients treated with modified radical prostatectomy (RP). Materials and Methods: A total of 184 patients with clinically high-risk PCa who underwent modified RP in a single Chinese center were retrospectively reviewed. Pelvic floor muscle training with biofeedback was routinely performed after catheter removal. UC was defined as wearing 0 or 1 protective pad daily. Univariate and multivariate Cox regression analyses were performed to determine the predictors of UC recovery. Results: The median age at surgery was 69.5 years (range 48-82), and the median follow-up duration was 40 months (range 12-111). Only 40 patients (21.7%) received a nerve-sparing procedure. For patients with restored UC, the median time to continence was 1 month (range 1-24). UC recovery at 1 month, 6 months, 12 months and the most recent follow-up was observed in 99 (53.8%), 158 (85.9%), 171 (92.9%) and 174 (94.6%) patients, respectively. Multivariate Cox regression analysis showed that patient age < 70 years (hazard ratio 1.684, P = .003) and smaller prostate volume (hazard ratio 0.989, P = .036), but not the surgical approach or treatment with a nerve-sparing procedure, independently predicted UC recovery. Conclusion: Age < 70 years and smaller prostate volume were independent predictors of UC recovery in clinically high-risk PCa patients. The adverse factors of high-risk disease were not significantly associated with UC recovery. These results may help surgeons preoperatively counsel patients regarding expected UC outcomes following RP.